Integrating consumer traits is key to increasing uptake of improved crop varieties: Evidence and policy insights from seed sample packs and cooking events in Uganda - Van Campenhout, Bjorn; Nabwire, Leocardia; Kramer, Berber; Trachtman, Carly; Abate, Gashaw T. (International Food Policy Research Institute, 2024)
 Semi-subsistence farmers in developing countries often play dual roles as both consumers and producers of the same crops. Consequently, decisions regarding crop selection are influenced by a com bination of household consumption needs and market-oriented considerations.  In this policy note, we summarize findings from a field experiment suggesting that integrating con sumption-oriented traits such as taste, color, and ease of cooking alongside production advantages is crucial for driving demand for improved crop varieties.  The field experiment consists of two interventions designed to enhance the adoption of improved maize seed varieties among smallholder farmers in eastern Uganda. The first intervention involves providing farmers with free seed sample packs to plant and directly experience the production related benefits, such as higher yield potential and drought resistance. The second intervention consists of organizing cooking demonstrations and blind tasting sessions to compare maize from improved variety with local varieties, focusing on consumption traits like palatability, texture, and ease of cooking.  We find that the seed sample packs significantly enhance farmers' perceptions of the seed's production traits, while the cooking demonstrations improve appreciation for its consumption traits. We also find that the cooking demonstration and tasting session increased the use of fresh Bazooka seed, with some indications that this also led to higher maize productivity. On the other hand, farmers who received the sample packs are more likely to reuse/recycle the grain harvested from the sample pack as seed in the subsequent season, essentially crowding out the demand for fresh/purchased seed. We argue that this may be a rational response in the context of positive transaction costs related to the use of improved seed varieties